2016
DOI: 10.1177/2043610616676024
|View full text |Cite
|
Sign up to set email alerts
|

The role of parents in the engagement of young children with digital technologies: Exploring tensions between rights of access and protection, from ‘Gatekeepers’ to ‘Scaffolders’

Abstract: This study investigates the role played by parents as mediators of young children's access and engagement with digital technologies. In Belgium, Germany, Latvia and Portugal, qualitative in-depth interviews were conducted with 10 families in each country, including one child between 6 and 7 years old. Our findings show that parents of young children mainly play the role of 'gatekeepers' when it comes to facilitating and constraining access to and use of digital technologies. Parents' perceptions of the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 24 publications
1
41
0
17
Order By: Relevance
“…Secondly, most of the research on privacy is focused on how children share information about themselves in digital contexts, which can also jeopardize their safety (e.g. boyd, 2014; Davis and James, 2013;Lapenta and Jørgensen, 2015;Dias et al, 2016;Holloway and Green, 2016;Holloway et al, 2016). Privacy risks to young children, stemming from companies (18) .…”
Section: The Case For Studying the Privacy Of Very Young Children Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, most of the research on privacy is focused on how children share information about themselves in digital contexts, which can also jeopardize their safety (e.g. boyd, 2014; Davis and James, 2013;Lapenta and Jørgensen, 2015;Dias et al, 2016;Holloway and Green, 2016;Holloway et al, 2016). Privacy risks to young children, stemming from companies (18) .…”
Section: The Case For Studying the Privacy Of Very Young Children Andmentioning
confidence: 99%
“…In the last few years, some studies have focused on young children's (under eight years old) digital technology use via qualitative approaches (e.g. Holloway et al, 2013;Chaudron et al, 2015;Dias and Brito, 2016). This strand of research has indicated that a significant number of young children perform online activities in an autonomous way, and often without any parental co-use or supervision, leaving them vulnerable to privacy infringements.…”
Section: The Case For Studying the Privacy Of Very Young Children Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on parental mediation of digital technologies has revealed that parents with positive perceptions and attitudes toward digital media are more likely to adopt participating and instructional parental mediation styles, acting as scaffolders for the development of digital (and other) skills in children, while parents with negative perceptions and views about digital media are more likely to monitor, restrict and limit the digital practices of children (Nikken & Jansz, ; Valcke, Bonte, Wener, & Rots, ). Also, research shows that perceptions and attitudes are intricate in experiences, as parents who have higher education, higher income, and who are intense and skilled users of digital media themselves are more likely to have positive views on children using digital technologies (Brito et al, ; Dias et al, ). In our research, we intend to explore to which extent the perceptions and attitudes of parents act as drivers or barriers to the adoption of smart toys.…”
Section: Are Perceptions Shaping the Domestication Of Smart Toys?mentioning
confidence: 99%
“…Together with the fact that children go online on more personal devices, this situation makes families struggle in mediating their offspring's access to the Internet. 73 On the other hand, parents and families should respect the need of the young to enjoy private spaces in which to share thoughts, opinions and to unfold their personality. Privacy could be violated by parents keeping their offspring's cellphone under excessive control, perhaps even without the latter knowing about it.…”
Section: The Familymentioning
confidence: 99%